Effect of palm oil mill sterilization process on the physicochemical characteristics and enzymatic hydrolysis of empty fruit bunch - Simarani, Khanom; Hassan, Mohd Ali; Abd. Aziz, Suraini; Wakisaka, Minato; Shirai, Yoshihito (Knowledgia Review, Malaysia, 2009)
Sterilization process of oil palm fruits by-product can be satisfactorily used as alternative degradation method in production of value-added products from Empty Fruit Bunch (EFB). It could be considered as an auto hydrolysis technique in the regular pre-treatment methods. Other studies on lignocelluloses showed that they increase the pore volume of the wood which increases the available surface area for the enzyme. Changes in structure and properties of the EFB cellulose caused by sterilization were investigated by x-ray diffractometry and enzymatic hydrolysis of cellulosic biomass for fermentable sugar production (glucose). The enzymatic hydrolysis results showed that the highest hydrolysis of 53.77±1.38% (g/g biomass) conversion was obtained in EFB after 72 h incubation with glucose production, (Yp/x) of 12.55±0.33 g L-1. The increase in Crystallinity Index (CrI) of sterilized biomass increased the yield of glucose (g L-1) up to 44.55% compared to Fresh Fruit Bunches (FFB) as a control. Results obtained appear to be commercial significance showing the potential of sterilization process in a palm oil mill as a zero cost pre-treatment for the effective utilization of empty fruit bunch biomass for value added production from the palm oil industry.